Pengaruh Digital Marketing, Word Of Mouth Dan Brand Awerness Terhadap Minat Pembelian Produk BPR Sejahtera Batam - Wendy, Wendy; Purba, Tiurniari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
One of the banks in the city of Batam is known as PT. BPR Sejahtera Batam. A company that wants to survive in a competitive market needs help from customers. Banking customers need to have an interest in buying so that the products offered by the bank can run and operate. The main problem is the decreasing interest in purchasing BPR Sejahtera Batam products, which is known through the decrease in the number of active customers compared to the previous year. This is because digital marketing is not optimal, there is not enough discussion among the public and the ability of potential buyers to get to know BPR Sejahtera Batam is still weak. The aim of the research is to find out how much influence digital marketing, word of mouth and brand awareness partially and simultaneously have on interest in purchasing BPR Sejahtera Batam products. The population in this study were customers from BPR Sejahtera Batam KC Mitra Raya, totaling 199 customers based on the company's records of active customers in 2022. Simple random sampling technique was chosen as the sampling technique in the study reviewed. This research uses the Slovin formula to determine the number of samples with a sample size of 133 respondents. The results state that either partially or simultaneously digital marketing, word of mouth and brand awareness have a positive and significant influence on purchasing interest.